Role of erythrocytes and platelets in the hypercoagulable status in polycythemia vera through phosphatidylserine exposure and microparticle generation - Tan, Xiaoyan; Shi, Jialan; Fu, Yueyue; Gao, Chunyan; Yang, Xue; Li, Jianan; Wang, Wei; Hou, Jinxiao; Li, Huibo; Zhou, Jin (Thrombosis and Haemostasis, 2013)
The development of thrombosis in polycythaemia vera (PV) involves multifactorial processes including pathological activation of blood cells. Release of microparticles (MPs) by activated cells in diseases is associated with thrombotic risk, but relatively few data are available in PV. The aim of the present study was to investigate the increase in MP release and exposure of phosphatidylserine (PS) on the outer membrane of MP-origin cells in patients with PV, and to analyse their procoagulant activity (PCA). PS-positive MPs and cells were detected by flow cytometry, while PCA was assessed with clotting time and purified coagulation complex assays. We found that PV patients had elevated circulating lactadherin+ MPs, which mostly originating from erythrocytes, platelets, granulocytes, and endothelial cells, as well as increased PS exposing erythrocytes/platelets as compared to secondary polycythaemia patients or healthy controls. These PS-bearing MPs and cells were highly procoagulant. Moreover, lactadherin competed factor V and VIII to PS and inhibited about 90% of the detected PCA in a dose-response manner while anti-TF antibody did no significant inhibition. Treatment with hydroxyurea is associated with a decrease in PS exposure and lactadherin+ MP release of erythrocytes/platelets. Our data demonstrate that PV patients are characterised by increased circulating procoagulant MPs and PS exposing erythrocytes/platelets, which could contribute to the hypercoagulable state in these patients.
Keywords: Phosphatidylserine; microparticles; polycythaemia vera; lactadherin